2019
DOI: 10.1186/s12943-019-0954-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PI3K in cancer: mechanisms and advances in clinical trials

Abstract: Phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling is one of the most important intracellular pathways, which can be considered as a master regulator for cancer. Enormous efforts have been dedicated to the development of drugs targeting PI3K signaling, many of which are currently employed in clinical trials evaluation, and it is becoming increasingly clear that PI3K inhibitors are effective in inhibiting tumor progression. PI3K inhibitors are subdivided into dual PI3K/mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
884
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,177 publications
(897 citation statements)
references
References 277 publications
(250 reference statements)
9
884
0
4
Order By: Relevance
“…Another key therapeutic target is PI3K. Drugs targeting either a single isoform of PI3K (isoform-specific inhibitors) or all four isoforms (pan-PI3K inhibitors) are available [94]. Pan-PI3K inhibitors were the first generation of PI3K inhibitors, comprising GDC-0941, BKM120, PX866, ZSTK474, and BAY80-6946 (copanlisib) [94].…”
Section: (2) Pi3k Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key therapeutic target is PI3K. Drugs targeting either a single isoform of PI3K (isoform-specific inhibitors) or all four isoforms (pan-PI3K inhibitors) are available [94]. Pan-PI3K inhibitors were the first generation of PI3K inhibitors, comprising GDC-0941, BKM120, PX866, ZSTK474, and BAY80-6946 (copanlisib) [94].…”
Section: (2) Pi3k Inhibitorsmentioning
confidence: 99%
“…Drugs targeting either a single isoform of PI3K (isoform-specific inhibitors) or all four isoforms (pan-PI3K inhibitors) are available [94]. Pan-PI3K inhibitors were the first generation of PI3K inhibitors, comprising GDC-0941, BKM120, PX866, ZSTK474, and BAY80-6946 (copanlisib) [94]. The first phase I clinical trial of BKM120 in patients with solid tumors, including EC, demonstrated an encouraging clinical outcomes: preliminary antitumor activity, acceptable toxicity, and favorable pharmacokinetic profile (NCT01068483) [95].…”
Section: (2) Pi3k Inhibitorsmentioning
confidence: 99%
“…LY-294002 HL60 and MCF7 (1e-05) are potent inhibitors of Phosphatidylinositol 3-Kinases. PI3K inhibitors are effective in inhibiting tumor progression (Yang et al, 2019). LY294002 is also a BET inhibitor having both anti-inflammatories and anti-cancer properties.…”
Section: Application To Drug Designmentioning
confidence: 99%
“…By removing acetyl groups, HDACs reverse chromatin acetylation and alter transcription of oncogenes and tumor suppressor genes. 105,106 Therefore, the use of deep sampling approaches combined with Connectivity Map technologies (CMAP) allows fast finding of possible compounds and the design of new drugs that maximize the mechanisms of action needed to counteract the progression of the disease. The results obtained in this case study back the introduction of AI in Precision Medicine, since the drugs obtained are also currently being tested in TNBC.…”
Section: Trichostatin a (Tsa) Is A Potent And Specific Inhibitormentioning
confidence: 99%
“…Initially, metabolomic changes in plasma induced by different pathway inhibitors in preclinical studies from tumour and in non-tumour bearing mice were measured. These preclinical data sets were used to generate target and tumour specific metabolomic signatures which were assessed later with plasma samples from patients in a Phase I clinical trial (Ang et al 2017(Ang et al , 2016Sarker et al 2015;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%